Religious Service Paradigm in Managing Theological Seminary - Nugroho, Fibry Jati; Octavianus, Steaven; Yuono, Yusup Rogo; Sari, Dwi Novita (Economic and Bussiness Faculty, Dr Soetomo University, 2019)
STT is one of the formal higher education organizations in Indonesia which was built as a place to prepare prospective Christian religious leaders, both pastors and religious teachers with legal diplomas. STT has a different understanding and philosophy than other formal universities in Indonesia. Based on this phenomenon, this research will show how the religious service paradigm affects organizational behaviour in Indonesian’s theological Seminary (STT). This research is designing only to map the phenomena that occur in the field, in this case how the service paradigm influences organizational behaviour in STT institutions through observation and interview. It is found that the service organizational culture in the STT environment has a significant influence on the performance of its employees.